The best formulation of compounds contained in herbal plants as sunscreen: A review - Aliefman Hakim; Burhanuddin Burhanuddin; L. Rudyat Telly Savalas; Zelisa Nudia Fitri; Jono Irawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The harmful effects of exposure to light (UV) can be prevented by using sunscreen. This study aims to determine the best formulation contained in various herbal plants to be used as a manufacturing material sunscreen. The method in this study is the study of literature from the research journal database on the internet, namely through google scholar and Proquest University of Mataram. Sunscreens are assessed in terms of light protection factor expressed by the SPF value (Sun Protection Factor) to determine the effectiveness of sunscreen preparations or the ability to withstand UV rays. Several types of herbal plants that grow in various regions in Indonesia contain photoprotective bioactive compounds. Aromatic ginger (Kaempferia galanga L.) is a herbal plant widely used as an ingredient in sunscreens with a high protection category. Cinnamic derivatives, namely ethyl para-methoxycinnamate (EPMS), are one of the compounds contained in aromatic ginger and can be used as a manufacturing material sunscreen that is good and safe for the skin.